Ethics of age de-escalation in pediatric vaccine trials: Attending to the case of COVID-19. Issue 9 (24th February 2023) - Harbin, Ami; Laventhal, Naomi; Navin, Mark
Abstract: In the development of new vaccines, many trials use age de-escalation : after establishing safety and efficacy in adult populations, progressively younger cohorts are enrolled and studied. Age de-escalation promotes many values. The responsibility to protect children from potential risks of experimental vaccines is significant, not only given increased risks of adverse effects but also because parents and medical professionals have a moral responsibility to protect children from harms associated with novel, uncertain interventions. Further, given that young children cannot provide informed consent, acceptable risks for research requiring proxy consent are lower than for adults making decisions for themselves. Although age de-escalation approaches are widely used in vaccine trials, including notably in the recent development of pediatric COVID-19 vaccines, ethicists have not addressed the benefits and risks of these approaches. Their benefits are largely assumed and unstated, while their potential risks are usually overlooked. There are no official ethics guidelines for the use of age de-escalation in clinical research. In this paper, we provide a systematic account of key moral factors to consider when employing age de-escalation. Analyzing pediatric COVID-19 vaccine development as our key case study, we clarify the benefits, risks, and trade-offs involved in age de-escalation approaches and call for the development of evidence-based best practice guidelines to identify when age de-escalation is likely to be an ethical strategy in vaccine development.